A novel free fatty acid receptor 1 (GPR40/FFAR1) agonist, MR1704, enhances glucose‐dependent insulin secretion and improves glucose homeostasis in rats. Issue 4 (21st July 2017) - Tsuda, Naoto; Kawaji, Atsuko; Sato, Toshihiro; Takagi, Mitsuhiro; Higashi, Chika; Kato, Yutaka; Ogawa, Kumiko; Naba, Hiroyasu; Ohkouchi, Munetaka; Nakamura, Masaki; Hosaka, Yoshitaka; Sakaki, Junichi
Abstract: Activation of G protein‐coupled receptor 40/Free fatty acid receptor 1 (GPR40/FFAR1), which is highly expressed in pancreatic β cells, is considered an important pharmacologic target for the treatment of type 2 diabetes mellitus. The aim of this study was to determine the effect of MR1704, a novel GPR40/FFAR1 agonist, on glucose homeostasis in rats. MR1704 is a highly potent and selective, orally bioavailable agonist with similar in vitro potencies among humans, mice, and rats. Treatment of rat islets with MR1704 increased glucose‐dependent insulin secretion. Augmentation of glucose‐dependent insulin secretion was abolished by adding a GPR40/FFAR1 antagonist. In mouse, insulinoma MIN6 cells, palmitic acid induced the activity of caspase 3/7 after a 72‐h exposure, while pharmacologically active concentrations of MR1704 did not. In an oral glucose tolerance test in normal Sprague‐Dawley rats, orally administered MR1704 (1–10 mg·kg −1 ) reduced plasma glucose excursion and enhanced insulin secretion, but MR1704 did not induce hypoglycemia, even at 300 mg·kg −1, in fasted Sprague‐Dawley rats. In addition, orally administered MR1704 reduced plasma glucose excursion and enhanced insulin secretion in diabetic Goto‐Kakizaki rats. Oral administration of MR1704 once daily to Goto‐Kakizaki rats reduced their blood glucose levels during a 5‐week treatment period without reducing pancreatic insulin content; as a result, hemoglobin A1C levels significantly decreased. These results suggest that MR1704 improves glucose homeostasis through glucose‐dependent insulin secretion with a low risk of hypoglycemia and pancreatic toxicity. MR1704 shows promise as a new, glucose‐lowering drug to treat type 2 diabetes mellitus.